Resonance frequency estimation in series-to-series inductive power transfer - Adam, Ismail; Alanazi, Meshari D; Khan, Sheroz; Yaacob, Mashkuri; Nordin, Anis Nurashikin; Mansor, Hasmah; Habaebi, Mohamed Hadi (IEEE, 2024)
Inductive Power Transfer (IPT) finds applications in various fields that require episodic rather than continuous power supplies, such as implantable medical devices, consumer electronics, IoT applications, civil structure monitoring, and electric vehicle charging. The efficiency of IPT systems depends on the operating frequency which is determined by the coupling coefficient and is affected by the distance between the transmitting and receiving coils. Therefore, accurate estimation of the coupling coefficient and resonance frequency of the IPT is essential to ensure maximum power transfer. This paper presents a novel yet straightforward method for estimating the series-to-series resonant frequency of Inductive Resonant Power Transfer (IRPT) systems. The proof utilizes post-processed experimental data, combining Total Harmonic Distortion (THD) and RMS voltage (VRMS) values evaluated on the transmitter side and obtained through Fast Fourier Transform (FFT). The research shows that the resonant frequency can be determined by identifying the points of lowest THD and highest VRMS on the transmitting side. The analytical plots are experimentally validated by establishing a transmitter unit with a variable frequency pulse generator to drive a DC-to-AC converter connected to a primary coil and a capacitor. The setup includes a display unit and multiple input switches for manually adjusting frequency settings, as well as activating and deactivating the DC-to-AC converter in 10Hz, 100Hz, and 1kHz frequency steps. The study shows promising results in determining the IPT resonance frequency to maximize power transfer, paving the way for advances in inductive resonant Power Transfer applications, such as move-and-charge Wireless Power Transfer (WPT). The novelty of this study not only lies in the simplicity of the proposed technique but also in its feasibility and applicability to the real world application scenarios. The results of this work have applications in many wireless technologies, including IoT applications.